The impact of climate change on road and building infrastructure: a four-country study. Issue 4 (9th November 2015) - Chinowsky, Paul; Schweikert, Amy; Hughes, Gordon; Hayles, Carolyn S.; Strzepek, Niko; Strzepek, Kenneth; Westphal, Michael
Abstract : Purpose: – The purpose of this study is to examine the potential impact of climate change on the built environment in four Northern Asian countries. The impact on roads and buildings infrastructure in China, Japan, South Korea and Mongolia were considered during the decades 2030, 2050 and 2090. Design/methodology/approach: – The study is based on a stressor-response approach, where using the analysis of 17 Intergovernmental Panel on Climate Change (IPCC) approved Global Circulation Model (GCM) scenarios, projections for impacts from flooding events, precipitation amounts and temperature were determined. The cost of the impacts, based on both maintenance and new construction considerations, were then determined. "Adapt" and "No Adapt" scenarios were incorporated to predict potential costs in each era. Findings: – Mongolia is vulnerable under the majority of scenarios and faces the greatest opportunity cost in terms of potential loss to enhancing the road stock. China is also vulnerable, but the extent of this vulnerability varies widely based on the climate scenarios. Japan is primarily vulnerable to road stock impacts, although some scenarios indicate buildings vulnerability. South Korea appears to have the least vulnerability but could still face 1 billion annual costs from climate change impacts. Practical implications: – Results indicate the need for proactive policy planning to avoid costly impacts later in the century. Originality/value: – The study illustrates the diverse affects that may occur under climate change scenarios and the potential benefit gained from understanding and planning for the projected climate impacts on the built environment.